2015
DOI: 10.1123/jpah.2013-0215
|View full text |Cite
|
Sign up to set email alerts
|

Active Commuting by Bicycle: Results of an Educational Intervention Study

Abstract: We suggest taking these findings into consideration in further studies to understand better the role of educational intervention on active commuting by bicycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Four studies reported a change in the number of trips per transport mode [28,31,33,35] of which three reported a decrease in car trips, two reported an increase in public transport trips and/or trips by bike, and there was one each for increased walking or carpooling. Changes in the main transport mode were reported in five of the studies [9,31,34,35,36], showing an increase in bicycle use, walking, and the use of active transport modes in combination. Car use and public transport use were reported as decreasing due to the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies reported a change in the number of trips per transport mode [28,31,33,35] of which three reported a decrease in car trips, two reported an increase in public transport trips and/or trips by bike, and there was one each for increased walking or carpooling. Changes in the main transport mode were reported in five of the studies [9,31,34,35,36], showing an increase in bicycle use, walking, and the use of active transport modes in combination. Car use and public transport use were reported as decreasing due to the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…The units in which the outcomes were measured varied, thus making comparison difficult, especially when raw data was not provided. Surprisingly, only three studies focused on the progression to higher stages of change [9,27,31]. Four studies reported an improved willingness to use the target transport mode, reflecting a progression during the pre-action stages [28,30,33,34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-efficacy-the belief that individuals are able to execute behaviors that lead to desired outcomes-is a significant predictor of behavioral change [10]. In line with the soft approach, interventions often focus on reinforcing beliefs aligned with sustainable travel via group discussions, role-play, and information campaigns [14][15][16]. In recent years, many innovative projects have capitalized on evolving sustainability values, national or local policy frameworks that prioritize environmental concerns, or high-density cities with established or expanding public transport infrastructure to implement more sustainable travel (see for example [9,10,14,17]).…”
Section: Introductionmentioning
confidence: 99%